Molecular responses of Lotus japonicus to parasitism by the compatible species Orobanche aegyptiaca and the incompatible species Striga hermonthica - Hiraoka, Yukihiro (Journal of experimental botany, 2009)
Lotus japonicus genes responsive to parasitism by the compatible species Orobanche aegyptiaca and the incompatible species Striga hermonthica were isolated by using the suppression subtractive hybridization (SSH) strategy. O. aegyptiaca and S. hermonthica parasitism specifically induced the expression of genes involved in jasmonic acid (JA) biosynthesis and phytoalexin biosynthesis, respectively. Nodulation-related genes were almost exclusively found among the Orobanche-induced genes. Temporal gene expression analyses revealed that 19 out of the 48 Orobanche-induced genes and 5 out of the 48 Striga-induced genes were up-regulated at 1 dai. Four genes, including putative trypsin protease inhibitor genes, exhibited systemic up-regulation in the host plant parasitized by O. aegyptiaca. On the other hand, S. hermonthica attachment did not induce systemic gene expression